2018
DOI: 10.1080/15476286.2018.1474072
|View full text |Cite
|
Sign up to set email alerts
|

Global profiling of hnRNP A2/B1-RNA binding on chromatin highlights LncRNA interactions

Abstract: Long noncoding RNAs (lncRNAs) often carry out their functions through associations with adaptor proteins. We recently identified heterogeneous ribonucleoprotein (hnRNP) A2/B1 as an adaptor of the human HOTAIR lncRNA. hnRNP A2 and B1 are splice isoforms of the same gene. The spliced version of HOTAIR preferentially associates with the B1 isoform, which we hypothesize contributes to RNA-RNA matching between HOTAIR and transcripts of target genes in breast cancer. Here we used enhanced cross-linking immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 54 publications
2
48
0
Order By: Relevance
“…In MCF-7 ERα+ breast cancer cells, enhanced cross-linking immunoprecipitation (eCLIP) using antibodies specific to HNRNPB1 alone or HNRNPA2/B1 in combination identified 1,472 transcripts bound by both HNRNPB1 and HNRNPA2/B1, 899 transcripts uniquely bound by HNRNPB1, and 479 transcripts uniquely bound by HNRNPA2/B1 32 . HNRNPB1 binding sites revealed a preference for 5′-AGGAAGG-3′ versus 5′-UGGGGA-3′ for HNRNPA2/B1 32 . HNRNPA2/B1 binding peaks were primarily in chromatin samples, consistent with HNRNPA2/B1 binding to nascent transcripts 32 .…”
Section: Introductionmentioning
confidence: 99%
“…In MCF-7 ERα+ breast cancer cells, enhanced cross-linking immunoprecipitation (eCLIP) using antibodies specific to HNRNPB1 alone or HNRNPA2/B1 in combination identified 1,472 transcripts bound by both HNRNPB1 and HNRNPA2/B1, 899 transcripts uniquely bound by HNRNPB1, and 479 transcripts uniquely bound by HNRNPA2/B1 32 . HNRNPB1 binding sites revealed a preference for 5′-AGGAAGG-3′ versus 5′-UGGGGA-3′ for HNRNPA2/B1 32 . HNRNPA2/B1 binding peaks were primarily in chromatin samples, consistent with HNRNPA2/B1 binding to nascent transcripts 32 .…”
Section: Introductionmentioning
confidence: 99%
“…hnRNP A2/B1 has previously been suggested to be a reader of m6A, and the B1 isoform has a high affinity for binding HOTAIR 24,30,31 . However, comparing our previously generated eCLIP results for hnRNP B1 32 to the m6A eCLIP, both performed in MCF-7 cells, we found that, out of 10,470 m6A sites, only 417 (4%) were identified to contain an hnRNP B1 binding site within 1,000 nucleotides ( Figure S4A). Upon mapping hnRNP B1 signal intensity relative to the nearby m6A site, we observed that hnRNP B1 is depleted directly over m6A sites ( Figure S4B).…”
Section: Hnrnp B1 Is Not a Direct M6a Reader In Mcf-7 Cellsmentioning
confidence: 82%
“…Past researches have unveiled that RNA-binding proteins (RBPs) can interact with lncRNAs in tumors [23]. From starBase, we discovered that LINC00662 potentially bound with hnRNPC protein (Fig.…”
Section: Linc00662 Bound With Hnrnpc Protein and Had No Regulatory Inmentioning
confidence: 98%